Insights into urticaria in pediatric and adult populations and its management with fexofenadine hydrochloride - Ignacio J. Ansotegui (Allergy, Asthma & Clinical Immunology, 2022)
Abstract Objective The present narrative review provides a comprehensive update of the current knowledge on urticaria, both in adult and pediatric populations, and on the safety and efficacy of fexofenadine hydrochloride (HCl) as a treatment option. Data source A literature search was conducted on Embase and Medline. Study selection Clinical studies published in English and published between 1999 and 2020 were selected. Results Although the exact pathogenesis of urticaria is not fully understood, multiple pathways of mast cell activation are discussed to explain the existence of phenotypically different clinical manifestations of urticaria. An overview of the worldwide prevalence of chronic urticaria, including disease burden and patient’s quality of life is provided. The impact of urticaria on patient’s life differs on the basis of whether its form is acute or chronic, but pharmacological approaches are most often needed to control the disabling symptoms. A summary of the current management of urticaria recommended by different guidelines across countries (Global; European; American; Australian; Asian; Japanese) is presented. Non-sedating, second-generation H1-antihistamines are the preferred choice of treatment across several guidelines worldwide. Herein, the efficacy and safety of fexofenadine HCl, a representative second-generation H1-antihistamine approved for the treatment of urticaria, is discussed. The occurrence of urticaria manifestations in COVID-19 patients is also briefly presented. Conclusion The burden of acute and chronic urticaria is high for patients. Second generation anti-histamines such as fexofenadine HCl can help managing the symptoms.